NILAI PENDIDIKAN BUDI PEKERTI DALAM ANTOLOGI GEGURITAN LATHI KARYA EKO WAHYUDI - Ana, Harsiti Nur Fitri; Sulaksono, Djoko; Rahadini, Astiana Ajeng (Universitas Sebelas Maret, 2020)
This research is motivated by the importance of inculcating the value of character education to students through Javanese literary works of geguritan. The purpose of this study is to describe the value of character education contained in the anthology of Lathi geguritan by Eko Wahyudi. The method used in this research is descriptive qualitative. The data source in this study is the geguritan in the anthology of Lathi geguritan by Eko Wahyudi. The research data are in the form of words, phrases, clauses, sentences in geguritan which contain the value of character education. Data collection techniques using document analysis. Test the validity of the data using triangulation theory. The data analysis technique used is an interactive analysis technique using the Miles & Huberman model. The results of the study show that the values of character education contained in the anthology of Lathi geguritan by Eko Wahyudi include: religiosity, sociality, gender, justice, democracy, honesty, independence, fighting power, responsibility, and respect for the environment. Through geguritan in the anthology of Lathi's geguritan, the author wants to convey a message or message to the reader to become a complete human being with strong noble character.